Openness to Experience Trait Personality and Resilience to Coffee Shop Owners in Salatiga - Aisha Saverina Putri; Arthur Huwae (Universitas Pendidikan Ganesha, 2022)
When building or running a business, MSMEs actors often face various obstacles and risks, especially during the COVID-19 pandemic. This situation requires MSMEs actors to survive any situation so that the business can continue to run properly, as with the Coffee Shop owners in Salatiga. To be able to survive and face difficult times, individuals must be able to form a good personality with a positive outlook to innovate. Therefore, this study aims to see the relationship between the “openness to experience trait personality” and the resilience of Coffee Shop owners in Salatiga. This study uses a quantitative method with a correlation design. A total of 30 participants were involved using a saturated sampling technique. The measurement of the study used the BFI scale for “openness to experience trait personality” and the Connor-Davidson Resilience Scale (CD-RISC) resilience scale. The study's results prove a significant positive relationship between “openness to experience trait personality” and resilience in the coffee shop owners in Salatiga (r = 0.543 and significant 0.001). It indicates that the “openness to experience trait personality” is one of the factors related to the resilience of Coffee Shop owners in Salatiga.